The role of ulnar nerve subcutaneous anterior transposition during open reduction and internal fixation of distal humerus fractures: a retrospective cohort study - Abdulaziz F. Ahmed (14150082) (2022)
Purpose To compare the rates of ulnar nerve neuropathy following ulnar nerve subcutaneous anterior transposition versus no transposition during open reduction and internal fixation (ORIF) of distal humerus fractures. Methods This was a retrospective cohort study at an academic level I trauma centre. A total of 97 consecutive patients with distal humerus fractures underwent ORIF between 2011 and 2018. All included patients were treated with plates (isolated lateral plates excluded) and had no pre-operative ulnar neuropathy. Subcutaneous ulnar nerve anterior transposition was compared versus no transposition at the time of ORIF. The main outcome measure was the rate of ulnar nerve neuropathy. The secondary outcomes were the severity of the ulnar nerve neuropathy and the rate of ulnar nerve recovery. Results Twenty-eight patients underwent subcutaneous ulnar nerve anterior transposition during ORIF, whereas 69 patients had no transposition. Transposition was associated with significantly higher rates of ulnar nerve neuropathy (10/28 versus 10/69; P = 0.027). An adjusted logistic regression model demonstrated an odds ratio of 4.8 (1.3, 17.5; 95% CI) when transposition was performed. Ulnar nerve neuropathy was classified as McGowan grades 1 and 2 in all neuropathy cases in both groups (P = 0.66). Three out of ten cases recovered in the transposition group, and five out of ten cases recovered in the no transposition group over a mean follow-up of 11.2 months (P = 1.00). Conclusion We do not recommend performing routine subcutaneous ulnar nerve anterior transposition during ORIF of distal humerus fracture as it was associated with a significant 5-fold increase in ulnar nerve neuropathy. Other Information Published in: International Orthopaedics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00264-020-04745-0